Application management information systems in research and student activities: a case study of NAEM Vietnam - Quoc, Huu Dang; Van, Tien Phan; Viet, Ha Le; Dung, Nguyen Thi; Truong, Bui Quang (Institute of Advanced Engineering and Science, 2025)
The management information systems (MIS) for education bring many benefits to management at universities, educational institutions, and academies. The Vietnam National Academy of Education Management (NAEM) has successfully integrated information technology into the management, teaching, and learning process, bringing many benefits. Many professional activities have been included in the standard framework of the academy's faculties. However, more specific and detailed activities at specialized faculties are being actively researched and implemented for management purposes. This article presents a study on the construction and implementation of a management information system to support the management of activities at faculties, such as managing information about lecturers' teaching, information about scientific research activities, and published works, In addition, this system also allows students to engage in learning activities such as registering for internships and internships at enterprises, information about graduation thesis implementation, and lecturers' assignments to guide students. Deploying this system at faculties supports the management of detailed operations, improves data management and processing, and ensures consistency in management.